Pengaruh Promosi Kesehatan Kanker Serviks dengan Media Flashcard terhadap Motivasi WUS untuk Deteksi Dini Metode IVA - Kusumas Pratiwi, Sang Ayu Agung; Surinati, Dewa Ayu; Hartati, Ni Nyoman; Suratiah, Suratiah; Labir, I Ketut; Ruspawan, Dewa Made (Jurnal Gema Keperawatan, 2024)
Cervical cancer is still the second highest contributor to death after breast cancer in Indonesian women after breast cancer. The government has made various efforts to deal with the problem of cervical cancer, one of which is the early detection program. Early detection is the key to cancer prevention and treatment efforts  because it has a cure chance of up to 90% if detected early. Visual Inspection with Acetic Acid Application (IVA) is the first choice as a means of early detection that is in line with a comprehensive approach to cervical cancer prevention. However, the implementation of the program is not optimal, as evidenced by the low percentage of early detection coverage of cervical cancer IVA method. This is due to various factors, one of which is the low motivation of Women of Childbearing Age (WCA). WCA's motivation for early detection is greatly influenced by WCA's exposure to health information. An educational approach through health promotion is the main way to increase information exposure. The success of health promotion is certainly inseparable from the media used. One of the media with a good stimulus used in health promotion is flashcards. This study aims to determine the effect of cervical cancer health promotion with flashcard media on WCA motivation for early detection of the IVA method. The research design uses one group pretest-posttest with research instruments in the form of questionnaires. Sample selection used a purposive sampling technique with a sample of 54 people. Statistical tests using the wilcoxon test (α=0,05) show that p value = 0,000. Therefore, it was concluded that there was an effect of cervical cancer health promotion with flashcard media on WCA motivation for early detection of the IVA method.